2020
DOI: 10.1002/jcp.29435
|View full text |Cite
|
Sign up to set email alerts
|

α5‐nAChR modulates melanoma growth through the Notch1 signaling pathway

Abstract: The roles of α5‐nicotinic acetylcholine receptors (α5‐nAChRs) in various types of solid cancer have been reported; however, its role in melanoma remains unknown. We knocked down α5‐nAChR expression in melanoma cells to investigate the role of α5‐nAChR in the proliferation, migration, and invasion of melanoma cells, and its effect on downstream signaling pathways. Using immunohistochemical analysis, we determined that α5‐nAChR expression is significantly increased in human melanoma tissues and cell lines compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…EMT is regarded as a critical step in tumor invasion and metastasis [36]. A previous study suggested that CHRNA5 could regulate the migration and invasion ability of melanoma cells [23]. Similarly, our study indicated that CHRNA5 could enhance the invasion and metastasis ability of HCC by regulating EMT-associated genes.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…EMT is regarded as a critical step in tumor invasion and metastasis [36]. A previous study suggested that CHRNA5 could regulate the migration and invasion ability of melanoma cells [23]. Similarly, our study indicated that CHRNA5 could enhance the invasion and metastasis ability of HCC by regulating EMT-associated genes.…”
Section: Discussionsupporting
confidence: 62%
“…CHRNA5, upregulated in breast cancer, was identified as the secondary estrogen signaling network and exhibited prognostic value in breast cancer [22]. In melanoma, CHRNA5 was reported to modulate cancer growth by regulating the Notch1 signaling pathway [23]. Another study found that CHRNA5 could promote radioresistance via regulating E2F transcription factor activity in oral squamous cell carcinoma [24].…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, a recent report also demonstrated the involvement of α5-nAChR in the EMT process and tumor metastasis through regulating the Jab1/Csn5 signaling in lung cancer [ 45 ]. Another study revealed the role of α5-nAChR in regulating cell proliferation and migration in melanoma cells [ 46 ]. We further showed that α5-nAChR is essential of low-dose nicotine-induced EGFR phosphorylation as 100 nM nicotine had limited effect on phosphorylated EGFR when α5-nAChR was knocked down.…”
Section: Discussionmentioning
confidence: 99%
“…The nicotinic receptors have been studied in melanoma cells, highlighting the presence of multiple subunits such as α5/α9 / α3/ β4 [123,124,126,127]. Alpha-5 nicotinic receptors (α5-nAChR), one of the homopentameric nicotinic receptors, have been identified in different forms of solid tumors.…”
Section: The Nicotinic Receptors In Melanomamentioning
confidence: 99%
“…Alpha-5 nicotinic receptors (α5-nAChR), one of the homopentameric nicotinic receptors, have been identified in different forms of solid tumors. Performing an immunocytochemical analysis, it has been demonstrated that the expression of α5-nAChR is significantly increased in human melanoma tissue and melanoma cell lines, compared with normal human skin tissue [123]. The mechanism of action has been identified very recently; via the knockdown of the α5-nAChR expression in melanoma cells, it has been demonstrated that this receptor positively modulates cell proliferation, migration, and invasion.…”
Section: The Nicotinic Receptors In Melanomamentioning
confidence: 99%